Orthodontic camouflage with extractions of premolars in Class III Malocclusion. Case report - Lavado Torres , Ana Cecilia (2024)
This case report describes the orthopedic-orthodontic treatment of a 15-year-old adolescent attended the Dental Center at the University of San Martín de Porres, indicating that his chief complaint was the appearance of his smile. The patient presented a straight profile with a protruding lower lip and a class III skeletal malocclusion (ANB, -2 °), with class III occlusal relations, moderate-severe crowding, right posterior and anterior crossbite, and dentoalveolar compensations. The patient accepted an orthopedic treatment with maxillary expansion and protraction to manage the residual potential growth accompanied by orthodontic camouflage with extractions of the second upper premolars and first lower premolars. Treatment was started using a McNamara type expander, with an alternate expansion and constriction protocol for 7 weeks and was combined with the use of a Petit facial mask for 6 months. Meanwhile, the lower premolars were removed and the canines were retracted using a sectioned arch with conventional brackets. Subsequently, the rest of the fixed appliances were installed to align and level the dental arches. Once the cross bites were solved, the upper premolars were extracted and the spaces were closed with chains and Class III elastics. The total active treatment time was 36 months and it was possible to obtain an improvement of the skeletal pattern to a class I (ANB, 1 °), aligned and leveled dental arches together with a mutually protected occlusion. Follow-up after 20 months indicated that the results of the treatment were quite stable.